Modeling of oxygen transfer correlations for stirred tank bioreactor agitated with atypical helical ribbon impeller - Mohamed, Mohd Shamzi; Mohamad, Rosfarizan; Ramanan, Ramakrishnan Nagasundara; Abdul Manan, Musaalbakri; Ariff, Arbakariya (Science Publications, 2009)
Problem Statement: Mixing filamentous fungi entails delicate balance between promoting high volumetric oxygen transfer coefficient (kLa) while keeping low hydrodynamic stresses in the microenvironment of cultures. This study examined the oxygen transfer capability of a prototype low shear helical impeller as a potential replacement for the standard Rushton turbine. Approach: The dependence of kLa upon specific power uptake, superficial gas velocity and apparent viscosity were examined under coalescent, non-coalescent and viscous pseudoplastic fluids scenario using dynamic gassing out technique. Subsequently, collected data were treated under historical data design of response surface methodology. Results: Three empirical power law kLa correlations were developed for each fluid. Correlation comparison with literature models for single turbine agitation suggest higher kLa augmentation within 1.5-3.6 folds for helical impeller in distilled water and as high as 78% improvement in electrolytes fluid. However impeller performance is comparatively 10% lower against theoretical kLa of triple turbines arrangement for power uptake between 0-1600 W m-3. In case of carboxymethylcellulose, better oxygen transfer is expected for design with higher proportionality of impeller-to-tank internal diameter. Conclusions: Helical impeller performance as gas-liquid contactor is comparable to single and triple Rushtons turbines, with superficial gas velocity proved to be more influential than power uptake in non-viscous liquids and vice versa in viscous pseudoplastic fluids.